Anthropometric and physiological characteristics of elite Serbian basketball players - Mazic, S.; Suzic, J.; Dikic, N.; Ostojic, S.; Djelic, M.; Ilic, V.; Nesic, D.; Radovanovic, D. (Archivos de medicina del deporte, 2008)
Aim: The purpose of this study was to describe anthropometric and physiological characteristics of elite Serbian basketball players and to evaluate whether players in different positional roles have different physical and physiological profi les. Materials and methods: Over six years we performed 702 functional testing and examined 256 basketball players from First National League as well as National team. We measured Body Height (BH), Body Weight (BW), percentage of Body Fat (%BF), by BIA and skinfolds method and Percentage of Muscles (%M). We also performed maximal incremental protocol on treadmill, method breath by breath (Jaeger, Oxycon Pro) and determined Maximal Oxygen Consumption (VO2max) . We recorded Heart Rate at rest (HR), at the end of the test (HRmax), at anaerobic threshold (HRAT), during recovery in 1st and 3rd minute (HR 1min, HR 3min). Results: Average age was 21,57±4,58 years, BH 199,11±8,54 cm, BW 94,45±12,44 kg, % BF 10,41±3,98, %M 50,93±2,78, HR 63,11±10,63 bpm, VO2max 53,07±6,21 ml/minkg, HRmax 184,46±10,54 bpm, HRAT 177,14±10,87 bpm, HR1min 145,15±15,33 bpm, HR3min 108,81±15,16 bpm. Conclusion: Anthropometric and functional characteristics of the elite basketball players varied among different positional roles. According to the references, the results of the present study demonstrate that a strong relationship exists between anthropometric and physiological characteristics of Serbian and Greek and Lithuanian basketball players.